Non-volatile FPGA architecture using resistive switching devices - Ho, Patrick W. C. (2017)
This dissertation reports the research work that was conducted to propose a non-volatile architecture for FPGA using resistive switching devices. This is achieved by designing a Configurable Memristive Logic Block (CMLB). The CMLB comprises of memristive logic cells (MLC) interconnected to each other using memristive switch matrices. In the MLC, novel memristive D flip-flop (MDFF), 6-bit non-volatile look-up table (NVLUT), and CMOS-based multiplexers are used. Other than the MDFF, a non-volatile D-latch (NVDL) was also designed. The MDFF and the NVDL are proposed to replace CMOS-based D flip-flops and D-latches to improve energy consumption. The CMLB shows a reduction of 8.6% of device area and 1.094 times lesser critical path delay against the SRAM-based FPGA architecture. Against similar CMOS-based circuits, the MDFF provides switching speed of 1.08 times faster; the NVLUT reduces power consumption by 6.25nW and improves device area by 128 transistors; while the memristive logic cells reduce overall device area by 60.416μm2. The NVLUT is constructed using novel 2TG1M memory cells, which has the fastest switching times of 12.14ns, compared to other similar memristive memory cells. This is due to the usage of transmission gates which improves voltage transfer from input to the memristor. The novel 2TG1M memory cell also has lower energy consumption than the CMOS-based 6T SRAM cell. The memristive-based switch matrices that interconnects the MLCs together comprises of novel 7T1M SRAM cells, which has the lowest energy-delay-area-product value of 1.61 among other memristive SRAM cells. Two memristive logic gates (MLG) were also designed (OR and AND), that introduces non-volatility into conventional logic gates. All the above circuits and design simulations were performed on an enhanced SPICE memristor model, which was improved from a previously published memristor model. The previously published memristor model was fault to not be in good agreement with memristor theory and the physical model of memristors. Therefore, the enhanced SPICE memristor model provides a memristor model which is in good agreement with the memristor theory and the physical model of memristors, which is used throughout this research work.